Botulinum toxin-A injection improves motor recovery in patients with stroke (Annals of Medical Research, 2023)
Aim: Spasticity that occurs after a stroke may contribute to disability. Botulinum toxin type-A (BTX-A) injections are commonly used to manage spasticity. This study sought to determine the effectiveness of BTX-A injections on spasticity and motor recovery in patients with stroke.Materials and Methods: Twenty-five patients with stroke scheduled for BTX-A injection for spasticity were included in the study. The patients were analyzed in two groups: upper limb and lower limb group. A single dose of BTX-A  was applied to the patients. Before, 2, and 12 weeks after BTX-A injections, motor function was assessed using Brunnstrom recovery stages, and spasticity was evaluated according to Modified Ashworth Scale (MAS). The lower limb group additionally underwent the Functional Ambulation Classification (FAC) and 10-meter walking test.Results: Mean age of patients was 54.96 ± 12.84 years.  Eighteen patients were enrolled in the upper limb group and 23 in the lower limb group. Clinical evaluation of the upper limb group two weeks after injections demonstrated a significant decrease in shoulder adductor muscle MAS, elbow, wrist, and finger flexor muscles MAS, and a significant improvement in Brunnstrom recovery stages for the upper limb and hand (p
Keywords: Botulinum toxins type A injection; Spasticity; Stroke